2018
DOI: 10.1088/1361-6463/aacf10
|View full text |Cite
|
Sign up to set email alerts
|

Low-pressure discharges with hollow cathode and hollow anode and their applications

Abstract: The review relates to low-pressure discharges with a hollow cathode and a hollow anode. The term ‘low pressure’ implies that a neutral particle density is extremely small and the electron free path for ionization is in excess of the characteristic size for the discharge gap. On the other hand, the neutral particles still play an essential role in forming the gas-discharge plasma. Thus, the discharge regimes keep an intermediate position between the classical low-pressure discharge with avalanche ionization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(26 citation statements)
references
References 91 publications
0
26
0
Order By: Relevance
“…Due to the etching, the cutting edge radius diminishes to ≈3−4 µm from the minimum value of ≈10−11 µm available with the tool sharpening through grinding. The sharpening occurs due to a quite homogeneous sputtering of the tool surface near the edge at low gas pressure p < 1 Pa. Homogeneous plasma inside the chamber is generated by the glow discharge with a large hollow cathode [48], which is the vacuum chamber itself.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the etching, the cutting edge radius diminishes to ≈3−4 µm from the minimum value of ≈10−11 µm available with the tool sharpening through grinding. The sharpening occurs due to a quite homogeneous sputtering of the tool surface near the edge at low gas pressure p < 1 Pa. Homogeneous plasma inside the chamber is generated by the glow discharge with a large hollow cathode [48], which is the vacuum chamber itself.…”
Section: Discussionmentioning
confidence: 99%
“…Methanol steam reforming (R1), [2] CH OH + H O CO + 3H , also believed as the combination of methanol decomposition or pyrolysis (R2), [3] CH OH CO + 2H , offers higher hydrogen atom utilization [4] than its partial oxidation (R4), [5] CH OH + 0.5O CO + 2H , 3 2 2 2 → (R4) and, thus, is more suitable for hydrogen infrastructure. For distributed hydrogen production, the nonthermal plasma reforming technique [6][7][8][9][10][11][12][13][14][15][16] has greater advantages than conventional catalysis, due to its compact configuration and rapid response. Many studies on hydrogen production from methanol-reforming have been reported using nonthermal plasmas, such as microwave discharge, [17][18][19] gliding arc (GA) discharge, [20][21][22][23] dielectric barrier discharge (DBD), [24][25][26] and corona discharge, [27] including a few of mechanism research based upon density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…They are used to etch the surface, as well as to accompany the deposition of coatings [14]. Glow discharge with a cold hollow cathode enables the filling of the chambers with homogeneous plasma and ion-plasma processing of products immersed therein [15,16]. The present research is aimed at a combined hardening of machine parts in this plasma, which determines their surface nitriding and the deposition of hard wear-resistant coatings.…”
Section: Introductionmentioning
confidence: 99%